Сardiac interoception and its link with psychological characteristics in patients with symptomatic and asymptomatic premature ventricular contractions - A. S. Limonova; I. A. Minenko; A. A. Sukmanova; K. V. Davtyan; A. I. Ershova; O. M. Drapkina (Рациональная фармакотерапия в кардиологии, 2025)
Aim. To explore cardiac interoception (probed by interoceptive accuracy in the mental tracking task) and its association with psychological characteristics in groups of patients with symptomatic and asymptomatic premature ventricular contractions (PVC) and controls.Material and methods. The study included 34 patients with PVC [17 individuals formed the group with symptomatic PVC (median age: 43 years) and 17 — formed the group with asymptomatic PVCs (median age: 42 years)] and 17 healthy subjects without cardiovascular diseases (median age: 40 years) in the control group. All study participants underwent 24-hour blood pressure and Holter monitoring. Interoception was assessed by interoceptive accuracy probed by behavioral test — mental tracking task. Participants completed questionnaires to assess levels of depression, anxiety, alexithymia and body perception.Results. Patients with symptomatic PVC had significantly higher levels of personal (p<0.001) and situational (p=0.011) anxiety compared to controls (p<0.001). The total alexithymia index was elevated in both symptomatic (p=0.004) and asymptomatic patients (p=0.028) compared to controls. Body perception (supradiaphragmatic scale of the Body Perception Questionnaire) was significantly higher in the group with symptomatic PVC compared to both the asymptomatic group (p=0.003) and the control group (p<0.001). A trend towards higher interoceptive accuracy was found in the group with symptomatic PVC (p=0.021; after correction p=0.064). No correlation was found between the level of interoception and psychological characteristics.Conclusion. Our findings suggest a possible role of cardiac interoception in the development of PVC symptoms, which may serve as a basis for the development of non-invasive and non-pharmacological treatment methods aimed at reducing the intensity of PVC symptoms, taking into account patients’ levels of anxiety, alexithymia and body perception.